2009
DOI: 10.1677/joe-08-0353
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA methylation in the tissue-specific expression of the CYP17A1 gene for steroidogenesis in rodents

Abstract: The CYP17A1 gene is the qualitative regulator of steroidogenesis. Depending on the presence or absence of CYP17 activities mineralocorticoids, glucocorticoids or adrenal androgens are produced. The expression of the CYP17A1 gene is tissue as well as species-specific. In contrast to humans, adrenals of rodents do not express the CYP17A1 gene and have therefore no P450c17 enzyme for cortisol production, but produce corticosterone. DNA methylation is involved in the tissue-specific silencing of the CYP17A1 gene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 53 publications
1
47
1
2
Order By: Relevance
“…Epigenetic mechanisms have been described to establish tissue-specific gene expression through chromatin modification and remodeling (Li 2002;Missaghian et al 2009), and histone modifications are well known to be stably introduced during cellular differentiation (Li 2002;van Arensbergen et al 2010) and to profoundly alter the transcriptional activity of genes. Therefore, we tested whether the differentiation-dependent repression of certain housekeeping genes is similarly dependent on changes in chromatin structure.…”
Section: Mechanisms For Disallowancementioning
confidence: 99%
“…Epigenetic mechanisms have been described to establish tissue-specific gene expression through chromatin modification and remodeling (Li 2002;Missaghian et al 2009), and histone modifications are well known to be stably introduced during cellular differentiation (Li 2002;van Arensbergen et al 2010) and to profoundly alter the transcriptional activity of genes. Therefore, we tested whether the differentiation-dependent repression of certain housekeeping genes is similarly dependent on changes in chromatin structure.…”
Section: Mechanisms For Disallowancementioning
confidence: 99%
“…In humans, the expression of CYP17A1 is driven by a complex interaction of different transcription factors (TFs) and, differently from rodents [25] , it appears not directly influenced by epigenetic regulation [26,27] . Indeed, CpG islands, the sites of the epigenetic methylation, are absent in human CYP17A1 gene [25] . Indirect epigenetic control is however suggested by studies on the inductive effect of 5aza-dC on TFs required for CYP17A1 expression [28] .…”
Section: Cyp17a1mentioning
confidence: 99%
“…Initial studies of CpG methylation came from studies of bovine and rodent adrenals (Hornsby et al 1992). Missaghian et al (2009) have shown that, in rodent adrenals, methylation of the CYP17A1 promoter region is correlated with the silencing of gene expression and the production of corticosterone as the main glucocorticoid. The absence of a CpG island in the human CYP17A1 gene suggests that the direct epigenetic regulation of the CYP17A1 promoter is more essential in rodents and, therefore, that the expression of CYP17A1 in humans is driven by the above-mentioned complex interaction of transcription factors (MartinezArguelles and Papadopoulos 2010).…”
Section: Cyp17a1 Genementioning
confidence: 99%
“…According to the structural model of CYP17A1, it is composed of 508 amino acids, with 4 important structural domains, includ ing a substrate-binding domain, a catalytic activity area, a haem-binding region and a redox-part ner binding site (Auchus and Miller 1999;Auchus 2001). It is localized to the endoplasmic reticulum in the adrenal glands, testicular Leydig cells and ovarian thecal cells and lies at the crossroads of sex steroid and glucocorticoid synthesis (Missaghian et al 2009). Human Inhibitors of CYP17A1 in the pathway are also indicated.…”
Section: Introductionmentioning
confidence: 99%